2020
DOI: 10.1002/sscp.201900107
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and optimization of new high performance thin‐layer chromatography method for quantitation of Retapamulin in pharmaceutical formulation: Application of design of experiment

Abstract: The objective of the present study was to design, develop and optimize Design of Experiments supported high performance thin-layer chromatography method for quantitative estimation of Retapamulin in marketed cream and microemulsion formulations. Design of Experiments help to identify and understand the effect of important factors on response with minimum experimental run in developing robust method. To optimize chromatographic conditions and to study their effects on separation of Retapamulin, Box-Behnken expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As per the literature review, a specific HPTLC method Validated for estimation of MOM and OLO methods is available [51].…”
Section: Introductionmentioning
confidence: 99%
“…As per the literature review, a specific HPTLC method Validated for estimation of MOM and OLO methods is available [51].…”
Section: Introductionmentioning
confidence: 99%
“…This drug comes in the form of eye drops and is commonly prescribed to relieve symptoms such as itching, redness, and watering of the eyes caused by allergies like hay fever or allergic conjunctivitis [20][21][22]. Most of the detection approaches for OLP are chromatographic approaches [23][24][25][26][27][28][29][30][31][32][33]. While these methods provide outstanding detection limits and the capability to analyze OLP degradation by-products, their use is constrained by timeintensive procedures, extended pretreatment steps of the designated compounds or drug, and the need for exceptionally highpurity solvents, along with a requirement for skilled personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Olopatadine is official in Indian Pharmacopoeia [2] and US Pharmacopoeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [4–14], LC [14], HPLC [12, 1517], voltammetry [20], HPTLC [15, 1819, 22], stability‐indicating HPLC method [17], and LC‐ESI‐MS‐MS[21] for the estimation of OLO in pharmaceutical formulations. Fluticasone propionate (FLU) Figure 1, chemically [(6 S ,8 S ,9 R ,10 S ,11 S ,13 S ,14 S ,16 R ,17 R )−6,9‐difluoro‐17‐(fluoromethylsulfanyl‐carbonyl)−11‐hydroxy‐10,13,16‐trimethyl‐3‐oxo‐6,7,8,11,12,14,15,16‐octahydrocyclopenta‐[a]phenanthren‐17‐yl] propanoate Trifluorinated Gluco‐corticoid receptor with anti‐allergic and anti‐inflammatory effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…official in Indian Pharmacopoeia [2] and US Pharmacopoeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [4][5][6][7][8][9][10][11][12][13][14], LC [14], HPLC [12,[15][16][17], voltammetry [20], HPTLC [15,[18][19]22], stabilityindicating HPLC method [17], and LC-ESI-MS-MS [21] for the estimation of OLO in pharmaceutical formulations. Fluticasone propionate (FLU) Figure 1 thren-17-yl] propanoate Trifluorinated Gluco-corticoid receptor with anti-allergic and anti-inflammatory effect [23].…”
Section: Introductionmentioning
confidence: 99%